2022
DOI: 10.1002/tqem.21872
|View full text |Cite
|
Sign up to set email alerts
|

Elemental distribution of latex‐based aerobic granules and its effects on micromorphological properties and settling performance

Abstract: This study focuses on the settling profile and chemical characteristics of latex aerobic granules cultivated from rubber industrial wastewater. Latex‐based aerobic granular sludge (AGS) was cultivated using sequencing batch reactor (SBR) in supplemented with synthetic wastewater (SW) as nutrients feeding for biogranulation process. The bioreactor was operated for 24 h with eight series of intermittent 3 h SBR cycles continuously. The SBR configuration comprises of five operation phases from SW feeding, aeratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Aini Dahalan et al. (2022) focused on the settling profile and chemical characteristics of latex aerobic granules cultivated from rubber industrial wastewater. Latex‐based aerobic granular sludge (AGS) was cultivated using sequencing batch reactor (SBR) supplemented with synthetic wastewater (SW) as nutrients for the biogranulation process.…”
Section: Waste Water Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Aini Dahalan et al. (2022) focused on the settling profile and chemical characteristics of latex aerobic granules cultivated from rubber industrial wastewater. Latex‐based aerobic granular sludge (AGS) was cultivated using sequencing batch reactor (SBR) supplemented with synthetic wastewater (SW) as nutrients for the biogranulation process.…”
Section: Waste Water Treatmentmentioning
confidence: 99%
“…The equations showed that the capacitance increased after periods of biocapacitor inactivity and decreased after periods of activity, which led to equivalent variations in current density. AiniDahalan et al (2022) focused on the settling profile and chemical characteristics of latex aerobic granules cultivated from rubber industrial wastewater. Latexbased aerobic granular sludge (AGS) was cultivated using sequencing batch reactor (SBR) supplemented with synthetic wastewater (SW) as nutrients for the biogranulation process.…”
mentioning
confidence: 99%